(untitled) (Eurasian Medical Research Periodical, 2022)
Cataract extraction is the most performed ophthalmic surgery in the world. Although the meres of effective prophylaxis have significantly evolved following the improvement in the understanding of the aseptic techniques and applying the protocols for surgical prophylaxis as well as the introduction of modern technology and antiseptics, there is still minor probability of an infectious complication after the surgical intervention. Post– cataract surgery endophthalmitis is a grave complication that can result in severe vision loss and, occasionally, loss of globe integrity. [1] The currently reported incidence of post– cataract surgery endophthalmitis is from 0.06% to 0.36%.[2,3,4]. This literature review is performed in order to compile the updated data on the given issue and enhance eyecare specialists’ theoretical knowledge on post-operative endophthalmitis through the materials that are provided in the article.